Breastfeeding practice, support, and self- efficacy among working mothers in a rural health clinic in Selangor - Abdul Rashid, Aneesa; Shamsuddin, Nurainul Hana; Raja Malek Ridhuan, Raja Dalila Athirah; Sallahuddin, Nurin Amalina; Devaraj, Navin Kumar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: In first six months of life, breastfeeding is the recommended form of feeding by the World Health Organisation for the growing child. To enable the working mother to continue this noble practice, adequate workplace breastfeeding support and self- efficacy is needed. This study aims to determine the prevalence of breastfeeding among working mothers of children aged three months to two years and factors associated with breastfeeding practice including workplace support and mother’s self-efficacy. Method: This is a cross sectional questionnaire study carried out in a rural Health Clinic in Selangor using socio-demographic data, Workplace Breastfeeding Support Scale (WBSS), and the Breastfeeding Self-Efficacy Scale Short Form (BSES-SF). This study was conducted for a period of three months from April to June 2015. The respondents were employed Malaysian mothers of healthy infants aged three months to two years. A total of 84 participants were involved in the study. Data analysis was done with SPSS 22. Results: The prevalence of breastfeeding among working mothers were high at 97.6%. We found significant association of breastfeeding practice with workplace breastfeeding support (p=0.005) and self-efficacy (p= 0.017). We also noted a significant correlation between breastfeeding workplace support and breast feeding self-efficacy (r= 0.40, p <0.01). Age, religion, ethnicity, educational level and place of employment were found to be not associated with breastfeeding practices. Conclusion: This study highlights the importance of workplace support and self-efficacy with workplace breastfeeding practices. Policymakers and stakeholders should provide a conducive and supportive environment to enhance breastfeeding among working mothers.